Peranan Kreativitas dan Inovasi dalam Meningkatkan Volume Penjualan Produk ‎Chick’n Mentai Burger, Pada Pranita Rasa Vegetarian - Mulyani, Melita; Soeprapto, Vishnuvardhana S. (Universitas Mataram, 2024)
Pranita Rasa Vegetarian Restaurant, located in Pluit, North Jakarta, has its own challenges in increasing the sales volume of its products, one of which is a non-animal (vegetarian) burger product called Chick'n Mentai Burger.The purpose of this study is to see whether creativity and innovation have an influence in increasing the sales volume of Chick'n Mentai Burger products. The research method used is quantitative. The population in this study is customers and consumers of Pranita Rasa Vegetarian Restaurant whose number is not known exactly. The sampling technique used in this study is n probability sampling. The results showed that creativity and innovation had a significant influence on the sales volume of Chick'n Mentai Burger products at Pranita Rasa Vegetarian Restaurant, Pluit, North Jakarta. Therefore, it is important for Pranita Rasa Vegetarian Restaurant to continue to encourage creativity and innovation in its product development as a strategy to maintain and increase competitiveness in the vegetarian fast food market. The results of the analysis show that efforts to introduce variety and innovation in products, including the development of new recipes, attractive presentations, and creative marketing strategies, provide a boost to increased consumer interest and sales volume.